Analysis of abnormal grain growth behavior during hot-press sintering of boron carbide. Issue 10 (July 2020) - Zhang, Mei; Zhou, Zhihui; Yuan, Tiechui; Li, Ruidi; Zhang, Weishan; Zhang, Yingjie; Wang, Minbo; Xie, Siyao
Abstract: Dense boron carbide bearings with a central through hole were fabricated by hot-press sintering. When the sintering temperature was above the critical grain growth temperature, an increase in the applied pressure at 2100 °C caused a distinct abnormal grain size region. Two grain growth mechanisms were explored; normal grain growth (NGG) is controlled by a grain boundary diffusion mechanism whereas the abnormal grain growth (AGG) pattern abides by the 'Bose–Einstein' grain growth law.